2018
DOI: 10.2147/cmar.s159105
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil–lymphocyte ratio is a predictor of prognosis in patients with castration-resistant prostate cancer: a meta-analysis

Abstract: BackgroundThe prognostic value of neutrophil–lymphocyte ratio (NLR) in patients with castration-resistant prostate cancer (CRPC) had been investigated in previous studies; however, the results remain inconsistent. This study was aimed to investigate the prognostic value of NLR in CRPC patients.Materials and methodsLiterature was identified from PubMed, Embase, Web of Science, and Cochrane, which investigated the relationship between pretreatment NLR and prognosis in CRPC patients. HRs for overall survival (OS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…In a recent phase III clinical trial of abiraterone acetate plus prednisone versus prednisone alone in patients with mCRPC, a biomarker panel containing CTC number and LDH level was shown to be a surrogate for OS at the individual-patient level [ 30 ]. NLR and PLR are inflammatory parameters that also confer poor outcomes in mCRPC [ 13 , 14 , 31 , 32 ] and are easily available from routine complete blood counts and more stable compared to absolute counts [ 33 ]. However, the additional prognostic value of NLR and PLR has never been evaluated in the context of CTCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent phase III clinical trial of abiraterone acetate plus prednisone versus prednisone alone in patients with mCRPC, a biomarker panel containing CTC number and LDH level was shown to be a surrogate for OS at the individual-patient level [ 30 ]. NLR and PLR are inflammatory parameters that also confer poor outcomes in mCRPC [ 13 , 14 , 31 , 32 ] and are easily available from routine complete blood counts and more stable compared to absolute counts [ 33 ]. However, the additional prognostic value of NLR and PLR has never been evaluated in the context of CTCs.…”
Section: Discussionmentioning
confidence: 99%
“…Walsh et al first discovered the prognostic value of neutrophil-lymphocyte ratio (NLR) in pre-operative colorectal cancer patients [ 8 ]. Since then, there has been increasing evidence regarding the prognostic value of NLR in other solid tumors [ 9 12 ], including CRPC [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…NLR combining of neutrophilia and lymphopenia represents systemic inflammatory response and immune response. It is an independent predictor of poor prognosis for several solid cancers including castration-resistant prostate cancer, cervical adenocarcinoma, lung cancer, and esophageal carcinoma 6467. Similarly, a study enrolling 84 consecutive penile cancer patients investigated the association between NLR with pathologic LNM and prognosis 24.…”
Section: Discussionmentioning
confidence: 99%
“…An increased NLR has been reported to be a predictor of survival and therapeutic effects in PCa irrespective of tumor stage and therapy. 10,24 Conversely, a large patient population study showed that preoperative circulating immune biomarkers such as the NLR and PLR were not associated with postoperative prognosis in black or white men who underwent radical prostatectomy. 25 As to the clinical significance of the PLR in PCa, a high PLR was correlated with poor disease-free survival and OS, irrespective of ethnicity, tumor stage, and treatment modality.…”
Section: Discussionmentioning
confidence: 99%